The evolution of population biology - Singh, Rama S. (Rama Shankar), 1945-; Uyenoyama, Marcy K., 1953- (Cambridge University Press, 2004)
This unique collection of essays deals with the foundation and historical development of population biology and its relationship to population genetics and population ecology on the one hand and to the rapidly growing fields of molecular quantitative genetics, genomics and bioinformatics on the other. Published in honor of Richard Lewontin.